Perbaikan Jalan Longsor dengan menggunakan Stuktur Penahan Tanah (Kasus Ruas Jalan Tanah Badantung-Kiliran Jao, Sijunjung, Sumatra Barat): Geotechnical - andriani andriani (Universitas Syiah Kuala, 2026)
The slope stability of hillside roads in West Sumatra is often affected by the combination of weak soil conditions, steep topography, and high rainfall, which increase the pore water pressure behind retaining structures. One of the critical locations is found along the Tanah Badantung–Kiliran Jao Road section in Sijunjung Regency, which has a slope inclination of approximately 55° and consists of silty sand soil. The initial analysis indicates a slope safety factor (FK) of less than 1.25, suggesting the need for an adaptive soil retaining structure that can respond to local geotechnical and hydrological conditions. This study develops an adaptive design of a Retaining Wall that combines a gravity-type wall, a gabion toe structure, and an integrated drainage system to reduce pore water pressure. The drainage system includes a granular layer, geotextile filter, perforated toe drain, and weep holes as discharge paths. The results show that adding a gabion with a height of 1–2 m and a stone unit weight of 18–22 kN/m³ increases the sliding safety factor from 1.29 to >2.0 and the overturning safety factor from 5.4 to >5.5, while the bearing safety factor slightly decreases but remains safe (FK ≥ 3). This adaptive design effectively improves slope stability and drainage efficiency in compact silty sand soils.